Experiences of Spanish nurses in the rollout of nurse prescribing: a qualitative study - Canet-Vélez, Olga; Jodar-Solà, Gloria; Martín-Royo, Jaume; Mateo, Enric; Casañas, Rocio; Galbany-Estragués, Paola (Frontiers in Public Health, 2023)
Nurse prescribing has legal recognition in Spain, after a long regulatory process, with confusing, changing legislation that does not fully coincide with the reality of nurses’ practice. There is currently no research available on how nurses have experienced the rollout of nurse prescribing. The objective of this study is to describe the experiences of nurses in the rollout of nurse prescribing in the province of Barcelona, Spain. A descriptive qualitative study with intentional sampling was carried out between March 2021 and July 2022. The data were collected through semi-structured individual interviews and discussion groups. The participants were 24 nurses working in the province of Barcelona who were accredited in nurse prescribing or involved in the rollout of nurse prescribing. The data were analysed using thematic analysis, following Braun and Clark. The COREQ checklist was used to report findings. We describe nurses’ responses on the following themes: internal and external barriers; strategies to support nurse prescribing in the initial rollout and proposals for improvement; and factors linked to nurses’ satisfaction. The regulatory process has provided a safety framework for nurse prescribing. Strategies are needed for its comprehensive development and its acceptance among the public. The findings give visibility to nurse prescribing internationally.